Intron-dependent formation of pseudouridines in the anticodon of Saccharomyces cerevisiae minor tRNA(Ile). - Szweykowska-Kulinska, Z (1994)
We have isolated and sequenced the minor species of tRNA(Ile) from Saccharomyces cerevisiae. This tRNA contains two unusual pseudouridines (psi s) in the first and third positions of the anticodon. As shown earlier by others, this tRNA derives from two genes having an identical 60 nt intron. We used in vitro procedures to study the structural requirements for the conversion of the anticodon uridines to psi 34 and psi 36. We show here that psi 34/psi 36 modifications require the presence of the pre-tRNA(Ile) intron but are not dependent upon the particular base at any single position of the anticodon. The conversion of U34 to psi 34 occurs independently from psi 36 synthesis and vice versa. However, psi 34 is not formed when the middle and the third anticodon bases of pre-tRNA(Ile) are both substituted to yield ochre anticodon UUA. This ochre pre-tRNA(Ile) mutant has the central anticodon uridine modified to psi 35 as is the case for S.cerevisiae SUP6 tyrosine-inserting ochre suppressor tRNA. In contrast, neither the first nor the third anticodon pseudouridine is formed, when the ochre (UUA) anticodon in the pre-tRNA(Tyr) is substituted with the isoleucine UAU anticodon. A synthetic mini-substrate consisting of the anticodon stem and loop and the wild-type intron of pre-tRNA(Ile) is sufficient to fully modify the anticodon U34 and U36 into psi s. This is the first example of the tRNA intron sequence, rather than the whole tRNA or pre-tRNA domain, being the main determinant of nucleoside modification.